วิเคราะห์ต้นทุนการกำจัดมูลฝอยติดเชื้อโดยผ่านการบำบัด และการกำจัดมูลฝอยติดเชื้อโดยไม่ผ่านการบำบัด ก่อนส่งออกนอกโรงพยาบาล : กรณีศึกษาโรงพยาบาลจุฬาลงกรณ์ สภากาชาดไทย - เบญจพร จิตรหาญ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of this cross-sectional descriptive study was to carry out cost analysis of treated and non-treated infectious waste disposal. The composition of infectious wastes were collected and segregated at the sample infectious waste generators. To estimate the quantity of infectious wastes. The relevant of cost data were collected retrospectively. The total cost of treated and non-treated infectious wastes were computed from capital cost, labor cost and material cost. The treatment technologies for this study were autoclaving and microwaving. The result found that infectious waste quantities were 1286.16 kg (from 11 department, 7 days) or 183.94 kg/day. The major component was cotton, gauze and bandage (41.8%). The laboratory room produced the highest quantity of infectious wastes (233.92 kg.), and the highest rate of infectious waste generations were the operating and delivery room (4.98 kg./patient/day). The infectious wastes that can be treated by autoclaving and microwaving were 94.17% and 97.29% respectively. The cost analysis revealed that the total cost of autoclaving with capacity of treatment 32 kg/hr. was 10,416,871.79 baht (average total cost 24.95 baht/kg.), total cost of autoclaving with capacity of treatment 907 kg/hr. was 9,996,329.26 baht (average total cost 23.92 bath/kg.), total cost of autoclaving with capacity 1,000 litre was 9,468,084.74 baht (average total cost 22.67 baht/kg)., while total cost of microwaving capacity of treatment 100 kg/hr. was 10,942,700.09 baht (average total cost 26.21 baht/kg.), total cost of microwaving with capacity of treatment 408 kg/hr. was 12,468.127.15 baht (average total cost 29.86 baht/kg.). Total cost of non-treated infectious wastes were 9,928,127.05 bath (average total cost 23.78 baht/kg). the earliest break even point of technology was autoclaving with capacity 1,000 litre (at 340,146.89 kg. or in 10 month) and the operating cost changing has more effect to total cost of infectious waste disposal than the capital cost changing and the infectious waste quantity changing. The results of this useful for the administrator to allocate budget for infectious waste management and to make decision on the alternative technologies of infectious waste treatment to reduce infectious wastes and reduce cost in the future.